Three-Dimensional Numerical Modeling of Local Scour Around Bridge Foundations Based on an Improved Wall Shear Stress Model - Peng Yu; Sheng Xu; Jiuchao Chen; Lingke Zhu; Jiale Zhou; Lie Yu; Zewen Sun (Journal of Marine Science and Engineering)
Currently, there are two primary issues with CFD simulations of local scour around bridge foundations using the RANS method. Firstly, the self-sustaining characteristics of turbulent boundary conditions at the inlet require special attention. Secondly, the simulated location of the maximum scour depth does not align with experimental observations. This paper employs the RANS method to model the hydrodynamic characteristics surrounding bridge piers. The sediment transport model and sediment-sliding model, considering any slope of the riverbed, were adopted to simulate the spatiotemporal evolution of local scour around the bridge foundation. Building on traditional methods and assuming local turbulence equilibrium, a self-sustaining model is theoretically derived. This model swiftly develops a balanced turbulent boundary layer, achieving a horizontally uniform flow field and effectively maintaining consistency between the inlet-given turbulent profile and physical reality. Additionally, by incorporating the velocity component of the downward-flow in front of the pier and the average shear stress around the pier into the excess shear stress model, the refined wall shear stress model accurately estimates the scouring contributions of the downward-flow and the horseshoe vortex system in this region. The numerical results including the maximum scour depth, location, and scour pit shape are consistent with experimental findings. The findings demonstrate that the numerical approach proposed in this study effectively addresses the issue of inadequate estimation of turbulent characteristics in scour pit at the leading edge of bridge piers using the RANS method. This method offers novel insights and approaches for addressing local scour issues in bridges and offshore wind turbines, as well as vortex-induced vibration issues in submarine pipelines.